Elevated TLR4 as Potential Biomarker for RMT-positive Subclinical Tuberculosis - Priyono, Riski Irawan Putra; Handono, Kusworini; Djajalaksana, Susanthy; Santosaningsih, Dewi (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Subclinical tuberculosis (TB) is often underdiagnosed due to the limited sensitivity of sputum-based diagnostics. Host-response biomarkers, particularly pattern recognition receptors (PRRs), offer a potential alternative. Toll-like receptor 4 (TLR4), scavenger receptor class B type 1 (SR-B1), and dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) are involved in the early recognition of Mycobacterium tuberculosis and may reflect initial immune activation under conditions of low bacillary burden and absent clinical symptoms. However, their diagnostic value in subclinical TB remains unclear. Therefore, this study was conducted to investigate their potential as biomarkers for subclinical TB.METHODS: Eighty-eight asymptomatic adults with a radiographic suspicion of pulmonary TB were classified into rapid molecular test (RMT)-positive and RMT-negative groups based on GeneXpert MTB/Rifampicin (RIF) results, which served as the reference standard. Blood samples were collected from the subjects, and their serum levels of TLR4, SR-B1, and DC-SIGN were measured using enzyme-linked immunosorbent assay (ELISA).RESULTS: TLR4 levels were significantly higher in the RMT-positive group (p=0.011), whereas SR-B1 and DC-SIGN showed no significant differences. TLR4 was the only biomarker with strong correlation with subclinical TB status (r=0.861, p<0.001). Based on logistic regression results, TLR4 was identified as the superior predictor with an area under the curve (AUC) of 0.937, 91.3% sensitivity, and 89.8% accuracy. Combining SR-B1 and DC-SIGN with TLR4 did not materially improve diagnostic performance over the TLR4-only model.CONCLUSION: TLR4 is a promising biomarker associated with RMT-positive status among individuals with suspected subclinical TB, with strong diagnostic performance. Patients with both RMT-positive results and elevated TLR4 levels may require closer monitoring for potential progression to active disease.KEYWORDS: subclinical tuberculosis, PRRs, TLR4, SR-B1, DC-SIGN, tuberculosis biomarker